Analisis profil pelajar pancasila dimensi mandiri di sekolah dasar se-kecamatan ngemplak kabupaten boyolali - Zuliana Nikmah Fatkhiyatul Munawaroh; Supianto Supianto (Didaktika Dwija Indria, 2025)
This study aims to describe the profile of Pancasila students in the independent dimension in elementary schools in ngemplak district boyolali. The research method used is descriptive quantitative which aims to describe the research variables based on the results of quantitative data analysis. The sample determination used purposive sampling with a sample of 202 students in grades V and VI in ngemplak district, boyolali regency consisting of 3 elementary schools, namely SDN 3 Manggung, SDN 1 Gagaksipat, and SDN 1 Sawahan. Data collection used a non-test method in the form of self-assessment. The instrument used has two key elements, namely Self-Understanding and Situations Faced and Self-regulation. The results showed that the Pancasila Learner Profile of the independent dimension of students with very good categories as many as 12 students with a percentage of 6%, good categories as many as 117 students with a percentage of 58%, sufficient categories as many as 48 students with a percentage of 24%, and less categories as many as 25 students with a percentage of 12%. The score of the Self-Understanding and Situation elements is lower than the score of the Self-Regulation element.